Peran Strategi Komunikasi dalam Kebijakan Lingkungan: Tinjauan Sistematis Terpadu dan Analisis Bibliometrik - Remon Astra Safela; Annisa Novita Sary; Yunia Wardi; Susi Evanita (Postgraduate, University of Mataram, 2026)
Environmental issues and the increasing urgency to achive sustainable development goals have highlighted the importance of effective communication strategies in environmental policy implementation. However, public resistance, low stakeholder participation, and ineffective policy dissemination remain major challenges in many countries. This study aims to conduct a systematic literature review related to the implementation of communication strategy in the field of environmental studies. This study uses a hybrid systematic literature review (SLR) and bibliometric analysis to investigate the role and communication strategy in environmental policy. VOSviewer and the PRISMA framework were used to evaluate 22 articles from the Scopus database (2017–2026). The results show that research in this field is still limited, indicating opportunities for further investigation. Communication strategies have been shown to significantly increase public acceptance of environmental policies, strengthen stakeholder participation, and encourage sustainable behavior change thru digital platforms, value-based framing, and participatory approaches. The main driving factors of effective communication include collaborative practices, adequate funding, and fair policy framing, while barriers include weak institutional structures, lack of community-based approaches, and negative public perception. The identified research gaps include the scarcity of longitudinal studies, limited research in developing countries, and inadequate interdisciplinary integration between environmental psychology and policy communication. These findings provide an evidence-based foundation for policymakers and researchers to enhance the effectiveness of environmental policy communication.